Câu 5:
\(\dfrac{x+y-2017z}{z}=\dfrac{y+z-2017x}{x}=\dfrac{x+z-2017y}{y}=\dfrac{x+y-2017z+y+z-2017x+x+z-2017y}{z+x+y}=\dfrac{-2015\left(x+y+z\right)}{x+y+z}=-2015\)
\(\Rightarrow\left\{{}\begin{matrix}x+y-2017z=-2015z\\y+z-2017x=-2015x\\x+z-2017y=-2015y\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}x+y=2z\\y+z=2x\\x+z=2y\end{matrix}\right.\)
\(P=\left(1+\dfrac{y}{x}\right)\left(1+\dfrac{x}{z}\right)\left(1+\dfrac{z}{y}\right)=\dfrac{x+y}{x}.\dfrac{x+z}{z}.\dfrac{y+z}{z}=\dfrac{2z.2y.2x}{xyz}=8\)